Management of laryngopharyngeal reflux in Brazil: a national surveys - Lechien,Jerome R. (2022)
Abstract Introduction: Studies assessing the management of laryngopharyngeal reflux by otolaryngologists have reported an important heterogeneity regarding the definition, diagnosis, and treatment, which leads to discrepancies in the management of the patient. Information about the current knowledge and practices of Brazilian otolaryngologists in laryngopharyngeal reflux is lacking. Objective: To investigate the trends in management of laryngopharyngeal reflux disease among Brazilian otolaryngologists. Methods: A survey was sent by email to the members of the Brazilian Association of Otolaryngology-Head Neck Surgery. This survey has initially been conducted by the laryngopharyngeal reflux study group of young otolaryngologists of the International Federation of Otolaryngological Societies. Results: According to the survey responders, the prevalence of laryngopharyngeal reflux was estimated to be 26.8% of patients consulting in otolaryngology and the most common symptoms were globus sensation, throat clearing, cough and stomach acid reflux. Nasal obstruction, Eustachian tube dysfunction, acute and chronic otitis media, vocal fold nodules and hemorrhage were considered not associated with laryngopharyngeal reflux by the majority of responders. About 2/3 of Brazilian otolaryngologists based the diagnosis of laryngopharyngeal reflux on the assessment of both symptoms and findings and a positive response to empiric therapeutic trials. Proton pump inhibitor utilized once or twice daily, was the most commonly used therapeutic scheme. Only 21.4% of Brazilian otolaryngologists have heard about nonacid and mixed laryngopharyngeal reflux and the awareness about the usefulness of multichannel intraluminal impedance pH monitoring (MII-pH) was minimal; 30.5% of responders did not consider themselves as well-informed about laryngopharyngeal reflux. Conclusion: Although the laryngopharyngeal reflux-related symptoms, main diagnostic and treatment approaches referred by Brazilian otolaryngologists are consistent with the literature, the survey identified some limitations, such as the insufficient awareness of the role of laryngopharyngeal reflux in many otolaryngological conditions and of the possibility of non-acid or mixed reflux in refractory cases. Future studies are needed to establish international recommendations for the management of laryngopharyngeal reflux disease.